2017
DOI: 10.1097/pr9.0000000000000628
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation inhibits trigeminal nociception in a rodent model of episodic migraine

Abstract: Noninvasive vagus nerve stimulation inhibited mechanical nociception and repressed the expression of proteins associated with sensitization of trigeminal neurons in a rodent model of episodic migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 69 publications
7
39
1
Order By: Relevance
“…The experimental design for the first episodic migraine model was based on a prior study and involves activation of sensitized trigeminal neurons in response to exposure to a pungent odor (23). Animals were placed under 3% isoflurane and received 10 injections of 10 µl of complete Freund's adjuvant (CFA, Sigma-Aldrich, St. Louis, MO; 1:1 in 0.9% sterile saline) into the upper trapezius.…”
Section: Sensitization and Activation Of Trigeminal Nociceptive Neuronsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental design for the first episodic migraine model was based on a prior study and involves activation of sensitized trigeminal neurons in response to exposure to a pungent odor (23). Animals were placed under 3% isoflurane and received 10 injections of 10 µl of complete Freund's adjuvant (CFA, Sigma-Aldrich, St. Louis, MO; 1:1 in 0.9% sterile saline) into the upper trapezius.…”
Section: Sensitization and Activation Of Trigeminal Nociceptive Neuronsmentioning
confidence: 99%
“…Animals were monitored for normal behaviors for a total of 8 days. To cause activation of trigeminal nociceptors, animals were exposed for 10 min to the volatile compounds from an oil extract obtained from California bay laurel tree leaves (CBL, World Spice, Seattle, WA) that was prepared as described previously (23).…”
Section: Sensitization and Activation Of Trigeminal Nociceptive Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of VNS have also been studied in the treatment of other pain‐inducing conditions such as migraines, osteoarthritis, and Crohn's disease. In animal studies, VNS decreased pain‐induced activation of neurons in the trigeminal nucleus caudalis in addition to reducing pain behavior and trigeminal allodynia . Case report data from patients with invasive VNS, uncontrolled small‐scale clinical studies and larger RCT's (EVENT, PRESTO) investigating nVNS have shown a reduced number of headaches per day and decreased pain intensity scores (preventive use).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, t-VNS duration lasted for 4 h per day during the 3 months study period [19]. In order to parallel acute and chronic head pain and to investigate possible VNS-induced changes in the trigemino-nociceptive system, several preclinical studies confirmed the clinical observed VNS responsiveness, although the precise pathways are not fully understood [20][21][22][23][24][25][26][27][28].…”
mentioning
confidence: 99%